اثر برنامج تعليمي – تعلمي وفقاً لمفاهيم الطاقة المتجددة والنانوتكنولوجي على التنور التكنولوجي عند طلبة قسم الكيمياء (Journal Of Educational and Psychological Researches, 2017)
The research aims to build an educational program - learning, according to the concepts of renewable energy and nanotechnology And knowledge of its impact on the technological enlightenment when the third phase students in the Department of Chemistry, and to verify the goal and put the researcher null hypothesis the following: No Statistically significant difference at the level (0.05) between the average scores of the experimental group students who are studying material nanotechnology and renewable energy program Altalima- learning and the average score for the control group of students who are studying the same article the usual way in technological enlightenment. The search was limited to the third row in the Department of Chemistry, College of Education, Science Pure students -bn Haytham for the academic year 2014-2015m, was preparing the content of scientific material to include renewable energy concepts and nanotechnology, with the two groups experimental design was chosen. One of them set the other part restraint Odhu post-test design was chosen for research and the Department of Chemistry in the College of Education, Pure Science - Ibn al-Haytham Sample deliberate research because it is more convenient to carry out the experiment, were selected Mjootain (A, B) at random to represent the experimental group of (24) students and two groups (C, D) to represent the control group of (23) students, and held them equal in the number of variables, the experimental group was taught according to the program Altalima- learning and studying the second (control) in the usual way by the subject teacher for both groups and to measure the impact of the program in technological enlightenment was built search tool created by of building technological enlightenment scale which consists of (36) Positive paragraph (2), paragraph revealing was sure of his sincerity and persistence, was applied experience over the first semester by a lecture and one to two hours a week and applied technological enlightenment scale dimensionally on the two groups on 28 / 29/01/2015 m respectively, and use the samples t-test (t-test) The Pearson correlation coefficient and averages as a means of statistical data processing results were that there is a difference statistically significant between the average scores of the experimental group students and average grades control group students in technological enlightenment scale in favor of the experimental group were rejected null hypothesis, and in the light of the results and put the researcher set of recommendations and proposals .